Propuesta de un plan de mejoramiento para la prevención y control de las pérdidas de circulación en la perforación de los pozos A y B en el campo Castilla de Ecopetrol S.A. (2018)
The investigation focuses in mud losses while drilling Well A and Well B from Castilla field. Root Cause Analysis is developed using several tools as Ishikawa Diagram and Fault Tree Diagram. It was found that the root cause was the use of outdated information related to the pore pressure and the fracture gradient. (Depletion of K1 Geological Unit). Additionally the impacts were identified using tools as the Interrelation Diagram and Transition Diagram. These impacts were higher costs, increased non-productive times and formation damage. Prevention and control strategies were established from different studies from all over the world for depleted reservoirs. The improvement plan was developed using the Transition Tree